Highly Efficient Electroreduction of CO2 on Nickel Single‐Atom Catalysts: Atom Trapping and Nitrogen Anchoring. Issue 49 (24th October 2019) - Mou, Kaiwen; Chen, Zhipeng; Zhang, Xinxin; Jiao, Mingyang; Zhang, Xiangping; Ge, Xin; Zhang, Wei; Liu, Licheng
Abstract: Construction of single atom catalysts (SACs) with high activity toward electroreduction of CO2 still remains a great challenge. A very simple and truly cost‐effective synthetic strategy is proposed to prepare SACs via a impregnation–pyrolysis method, through one‐step pyrolysis of graphene oxide aerogel. Compared with other traditional methods, this process is fast and free of repeated acid etching, and thus it has great potential for facile operation and large‐scale manufacturing. Both X‐ray absorption fine structure and high‐angle annular dark‐field scanning transmission electron microscopy images confirm the presence of isolated nickel atoms, with a high Ni loading of ≈2.6 wt%. The obtained 3D porous Ni‐ and N‐codoped graphene aerogel exhibits excellent activity toward electroreduction of CO2 to CO, in particular exhibiting a remarkable CO Faradaic efficiency of 90.2%. Density functional theory calculations reveal that free energies for the formation of intermediate *COOH on coordinatively unsaturated NiN sites are significantly lower than that on NiN4 site, suggesting the outstanding activities of CO2 electroreduction originate from coordinatively unsaturated NiN sites in catalysts. Abstract : A very simple and truly cost‐effective synthetic strategy for emerging single atom catalysts, through one‐step pyrolysis of graphene oxide aerogel, is reported. Compared with other traditional methods, this process is fast and free of repeated acid etching, and thus it has great potential for facile operation and large‐scale manufacturing.